Transcription factor TaPIL1-mediated iron accumulation in wheat - Yanjun Meng; Zijia Tian; Jiayi Fan; Zhouxiang He; Bo Yu; Changqing Du; Tiancai Guo; Qiang Ge; Guozhang Kang (Plant Science, 2026)

Oxidation patterns and stability mechanisms of marine oils revealed by oxidized triglyceride and phospholipid analysis using RPLC–Q-TOF - Nan Meng; Yaru Li; Peixu Cong; Yu Song; Yanjun Liu; Jie Xu; Changhu Xue (Food Research International, 2026)

Model-based inference of monsoonal moisture from stalagmite and tree-ring δ18O - Qiang Li; Yifan Wu; Jiachuan Wang; Yu Liu; Yanjun Cai; Haiwei Zhang; Liangcheng Tan; Jingyao Zhao; Changfeng Sun; Huiming Song; Yang Xu; Yueer Li; et al. (Quaternary Science Reviews, 2026)

Disrupting the cardiolipin oxidation-apoptosis axis: low-temperature, high-salinity depuration extends anhydrous storage in Pacific oysters - Nan Meng; Xinyu Cao; Yu Song; Peixu Cong; Yanjun Liu; Yi Liu; Changhu Xue; Jie Xu (Food Research International, 2026)

Elucidating the oxidation mechanism of phospholipid-based marine oils during storage: A new insight based on the analysis of oxidized phospholipids - Nan Meng; Peixu Cong; Xincen Wang; Yu Song; Yanjun Liu; Yaru Li; Jie Xu; Changhu Xue (Food Research International, 2026)

CircGABRB2_006 Drives Malignant Progression and EMT in Papillary Thyroid Carcinoma via the miR-296-5p/FGFR1 Axis - Chuan Wan; Yanjun Guo; Han Guo; Jingjing Zhu; Fangchao Liu; Yunyuan Zhang; Bingfei Cheng; Juanjuan Li; Ying Xin; Bingzi Dong; Weiwei Fu; Dongmei Meng; et al. (Biochemical Genetics, 2026)

Ephedplics E-I: three lignans and two benzofuran-type compounds from the roots of Ephedra sinica Stapf and their neuroprotective activity - Yunlong Dou; Bowen Zhang; Meng Li; Xiaolan Wang; Shuyan Liu; Yanjun Sun; Xiaoke Zheng; Weisheng Feng (Journal of Natural Medicines, 2026)

The impact of contract choice on the economic benefits of resource utilization of swine manure by pig farmers: a perspective from environmental regulation and financing constraints - Yanjun Jiang; Yue Zhang; Xuebing Bai; Shilong Meng; Ruiyao Ying (Environment, Development and Sustainability, 2026)

Potential mechanism of Lactiflorin in treating ulcerative colitis via modulation of the PI3K/AKT pathway: a study integrating network analysis, bioinformatics analysis, and experimental evidence - Mengjia Zhang; Haotian Li; Ningjuan Yan; Man Meng; Xiaolan Su; Yanjun Liu; Runhua Chen; Jianqin Yang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Food-derived inositol derivatives mitigate high-fat diet-induced adiposity by attenuating inflammation and promoting adipocyte browning in mice - Xiaochen Guo; Mengjie Xu; Linlin Liu; Qinghui Lin; Rui Gao; Ruoxuan Xu; Wei Yu; Zhongmei Liang; Pengfei Wu; Zehan Dong; Zhen Xie; Nan Meng; et al. (Food Bioscience, 2026)

The role of jasmonic acid in enhancing drought resilience in mangroves: from signaling to restoration - Yi Han; Muqadas Noor; Meng Ying Huang; Wenna Wang; Muhammad Anwar; Yanjun Du (South African Journal of Botany, 2026)

Characterization, in vitro digestion properties and antioxidant activity of tropical starch - gallic acid complex - Xu Wang; Jia Luo; Yuan Meng; Gang Wu; Yanjun Zhang (Food Chemistry, 2026)

Dietary patterns drive sphingolipid metabolic rewiring: Integrative insights from transcriptomics and sphingolipidomics - Shuo Yang; Nan Meng; Xincen Wang; Yanjun Liu; Peixu Cong; Changhu Xue; Jie Xu (Food Bioscience, 2026)

Multi-Scale Fractal Dimension Analysis of Pore Structure and Its Controlling Factors in Marine–Continental Transitional Shale of the Late Carboniferous Benxi Formation, Ordos Basin, China - Yanjun Meng; Xinyu Zhang; Qin Zhang; Zhen Qiu; Wanli Gao; Haojie Ma (Natural Resources Research, 2026)

Evolution of non-colinear fault systems from extension to transtension: Northern Dongying Sag, Bohai Bay Basin, East China - Meng Zhang; Kuihua Zhang; Shuang Song; Yanjun Cheng; Zhiping Wu (Journal of Asian Earth Sciences, 2026)

Unraveling the flavor evolution mechanism in liquid-smoked rainbow trout through integrated lipidomics and flavoromics - Junpeng Zeng; Nan Meng; Xiaowei Fan; Yu Song; Peixu Cong; Yanjun Liu; Changhu Xue; Jie Xu (Food Chemistry, 2026)

An eco-friendly Pickering emulsion gel loading white mustard essential oil for attract-and-kill control of Plutella xylostella larvae - Meng Xiao; Xirui Chen; Xiaoqin Zhao; Qiuxia Li; Chaoyi Peng; Xiaozhuo Chen; Yanjun Lin; Jingjing Li; Jinming Zhang (Chemical Engineering Journal, 2026)

Novel composite essential oil nanoemulsion stabilized via a dual strategy of covalent chemical bonding and compositional synergy: Application to hairtail (Trichiurus lepturus) preservation - Meng Wang; Keming Zhang; Yanjun Wen; Yujin Li; Changhu Xue; Zihao Wei (Food Chemistry, 2026)

Safe recycling of oxytetracycline fermentation residue by thermal pretreatment coupled with compost: Antibiotic degradation, resistance gene removal, nutrient release, and soil improvement - Guocheng Liu; Zhiying Li; Wenzhuo Xu; Lingyun Meng; Xicheng Yuan; Jinying Li; Xue Li; Qianwen Wang; Qinghua Yan; Shuaishuai Xin; Mengwei Xie; Yanling Chen; et al. (Journal of Environmental Chemical Engineering, 2025)

Enhanced COP absorption refrigeration using R-1243zf/phosphonium based ILs with compression assistance for low-grade heat - Yanjun Sun; Haiqi Zheng; Bohao Yin; Wenqiang Zhang; Jianjun Meng; Dianbo Xin; Xiaopo Wang; Maogang He (International Journal of Refrigeration, 2025)

Assessment of habitat characteristics in typical seagrass bed ecosystems along the coast of Changhai County, Dalian - Yuchen Chu; Jun Yang; Juncheng Yin; Jie Tian; Jun Song; Kaiting Zhi; Dan Zhao; Yan Wang; Yufeng Zhang; Yanjun Wang; Qian Sun; Quanxiang Meng; et al. (Acta Oceanologica Sinica, 2025)

Has the application of agricultural green technologies achieved carbon reduction? Evidence from China - Shilong Meng; Yanjun Jiang; Hongwu Sun; Yanfei Sha; Ruiyao Ying (Clean Technologies and Environmental Policy, 2025)

Molecular fingerprints of dissolved organic matter leached from microplastics over prolonged photochemical aging: Implications for aquatic carbon cycling - Zekun Zhang; Zhao Liang Chen; Yanjun Liu; Yuanbi Yi; Ruanhong Cai; Ming Ye; Mengyang Liu; Meng Yan; Kenneth M.Y. Leung; Ding He (Water Research, 2025)

Sunlight-driven hydrogen peroxide activation via copper hydroxyphosphate with broad spectrum response for imidacloprid degradation: Mechanism insight and DFT calculation - Haoran Zhang; Jiang Li; Yujiao Liu; Sihao Fu; Tianjie Su; Lingyu Meng; Yunfei Wang; Nian Ma; Guocheng Liu; Qinghua Yan; Yanjun Xin; Shuaishuai Xin (Chemical Engineering Journal, 2025)

Using an integrated model of the extended theory of planned behavior and the temporal self-regulation theory to explain the sugar-sweetened beverage consumption in college students - Zhiqing Hu; Rui Meng; Tongtong Sheng; Qiran Cao; Yanjun Sun; Jian Yin; Yuan He (Appetite, 2025)

Salting-induced lipid hydrolysis and oxidation in dried squid fillets: A mechanistic link to formaldehyde formation, color browning, and flavor alteration - Junpeng Zeng; Xiaowei Fan; Nan Meng; Yanjun Liu; Yu Song; Peixu Cong; Xiaoming Jiang; Jie Xu; Changhu Xue (Food Chemistry, 2025)

Changes in growth and transcriptome expression patterns in mandarin fish (Siniperca scherzeri) under different photoperiods - Jiao Li; Yong Wei; Jun Song; Jun Yang; Xu-Fang Liang; Ke Lu; Qiuling Wang; Ke-Xiang Wang; Kaiting Zhi; Dan Zhao; Yan Wang; Yufeng Zhang; et al. (Acta Oceanologica Sinica, 2025)

Sustainable treatment of solid titanium-gypsum-waste using acidic titanium-white-wastewater to produce high-value α-hemihydrate gypsum - Yuru Wang; Mengqi Xiang; Jiangmei Yi; Ye Wang; Wenxiang Tang; Yanjun Zhong; Hua Meng; Xiaodong Ma; Zhiyuan Chen (Hydrometallurgy, 2025)

Fabrication of TiO2/CuFeO2 composites for oxytetracycline degradation through heterogeneous photo-Fenton-like process under visible light - Xue Li; Jinying Li; Jiaying Song; Zhiying Li; Xicheng Yuan; Lingyun Meng; Wenzhuo Xu; Qianwen Wang; Qinghua Yan; Shuaishuai Xin; Chengzhi Zhou; Guocheng Liu; et al. (Journal of Environmental Management, 2025)

Evaluation of the Diametrical Core Deformation Analysis (DCDA) and Fracture Surface Morphology for In-Situ Stress Estimation - Qingsen Meng; Yanjun Shang; Jianjun Chi; Shengwen Qi; Muhammad Hasan; Xuetao Yi (Rock Mechanics and Rock Engineering, 2025)

A new method for total organic carbon prediction of marine-continental transitional shale based on multivariate nonlinear regression - Xinyu Zhang; Yanjun Meng; Taotao Yan; Jinzhi Zhong; Zhen Qiu; Weibo Zhao; Liangliang Yin; Haojie Ma; Qin Zhang (Frontiers of Earth Science, 2025)

Years of life lost attributable to air pollution, a health risk-based air quality index approach in Ningbo, China - Qiang Hao; Lin Zhang; Xiaodong Zhang; Yanjun Wang; Cuixian Zhang; Suyan Meng; Jinhua Xu; Lina Hao; Xia Zhang (International Journal of Biometeorology, 2025)

Insights into relationship of oxidative potential of particles in the atmosphere and entering the human respiratory system with particle size, composition and source: A case study in a coastal area in Northern China - Ruiyu Li; Caiqing Yan; Yingze Tian; Yan Wu; Ruizhi Zhou; Qingpeng Meng; Li Fang; Yang Yue; Yanjun Yang; Haibiao Chen; Lingxiao Yang; Wei Jiang (Journal of Hazardous Materials, 2025)

Insight into the mechanism of Maillard reaction and lipids mutually contribute to the flavor release of squid fillets during the drying process - Junpeng Zeng; Nan Meng; Yu Song; Xiaowei Fan; Xiaoming Jiang; Peixu Cong; Yanjun Liu; Changhu Xue; Jie Xu (Food Chemistry, 2025)

Activating the green revolution: farmland transfer and agricultural green technology innovation—evidence from China - Shilong Meng; Yanjun Jiang; Shiyan Qiao; Hongwu Sun (Environment, Development and Sustainability, 2024)

Estimation of Young’s modulus for rocks using a non-invasive CSAMT method - Muhammad Hasan; Yanjun Shang; Qingyun Di; Qingsen Meng (Bulletin of Engineering Geology and the Environment, 2024)

Investigation of high-risk antibiotic resistance bacteria and their associated antibiotic resistance genes in different agricultural soils with biogas slurry from China - Yi Lu; Junhui Wu; Jiwei Li; Zailin Du; Changai Zhang; Yanjun Chai; Zewen Jin; Zichuan Li; Jun Meng; Haifeng Zhuang; Lifeng Ping; Ming Hung Wong; et al. (Journal of Hazardous Materials, 2024)

Estimation of rock core indices for development of underground infrastructure using non-invasive geophysical methods - Muhammad Hasan; Yanjun Shang; Shengwen Qi; Qingsen Meng (International Journal of Rock Mechanics and Mining Sciences, 2024)

(1 1 1) Facet-dominant peracetic acid activation by octahedral CoO anchored hollow carbon microspheres for tetracycline degradation - Yanjun Pan; Qiang Zhou; Fanyue Meng; Qi Cao; Jixing Bai; Zhuzhu Zhang; Qingyu Liu; Huiyan Zhang (Chemical Engineering Journal, 2024)

National-scale Geochemical Survey: Distribution of chemical elements in stream sediment of South and Central Asia - Jun Hong; Guanglu Meng; Jing Zhang; Jifei Cao; Bin Wang; Yanjun Luo; Bo Yang; Xueqi Zhang; Domenico Cicchella (Journal of Geochemical Exploration, 2024)

Highly efficient peroxymonosulfate activation by CoFe2O4@attapulgite–biochar composites: Degradation properties and mechanism insights - Yanjun Pan; Fanyue Meng; Jixing Bai; Bing Song; Qi Cao (Journal of Environmental Chemical Engineering, 2024)

Comparison and analysis of mechanism of β-lactoglobulin self-assembled gel carriers formed by different gelation methods - Xiaolin Meng; Ying Wu; Wangruiqi Tang; Lei Zhou; Wei Liu; Chengmei Liu; Sangeeta Prakash; Yanjun Zhang; Junzhen Zhong (Food Chemistry, 2024)

Coal structure identification based on geophysical logging data: Insights from Wavelet Transform (WT) and Particle Swarm Optimization Support Vector Machine (PSO-SVM) algorithms - Zhongzheng Tong; Yanjun Meng; Jinchuan Zhang; Yaning Wu; Zhen Li; Dongsheng Wang; Xingqi Li; Guangxi Ou (International Journal of Coal Geology, 2024)

Investigation of the NH3 consumption and H2O/NO formation during the oxidation of n-heptane and iso-octane blended with ammonia - Dao Zheng; Zhimin Peng; Dong He; Meng Zhang; Jidong Li; Yanjun Ding; Yanjun Du (Fuel, 2024)

Mid-infrared absorption spectroscopy measurements and model improvements during the oxidation of ammonia/ethanol and ammonia/diethyl ether blends in a shock tube - Dao Zheng; Dong He; Yanjun Du; Meng Zhang; Jidong Li; Yanjun Ding; Zhimin Peng (Fuel, 2024)

Ocular topical application of alpha-glucosyl hesperidin as an active pharmaceutical excipient: in vitro and in vivo experimental evaluation - Linrong Yu; Qiliang Zhang; Liping Zhou; Yanjun Wei; Mengshuang Li; Xianggen Wu; Meng Xin (Drug Delivery and Translational Research, 2024)

Mechanism of Antidepressant Action of (2R,6R)-6-Hydroxynorketamine (HNK) and Its Compounds: Insights from Proteomic Analysis - Chaohui Zhen; Chong Wang; Yanjun Ma; Yuli Pang; Feiyue Cai; Jiali Meng; Yuefei He; Ping Xiao; Jianxi Liu; Xi Mei; Shupeng Li; Guanzheng Wu; et al. (Molecular Neurobiology, 2024)

Effects of gamma irradiation on the nutritional quality and physicochemical properties of Morchella angusticeps - Ailian Meng; Peng Gao; Pan Xu; Xin Jia; Jiang He; Yan Wang; Qian Chen; Yanjun Zhang; Yalu Qiu; Min Huang; Hao Chen (Food Bioscience, 2023)

Viscosity measurement and correlation of saturated solutions of R-290 with three lubricants - Yanjun Sun; Xingdan Wang; Shibiao Wang; Xiangzhao Meng (International Journal of Refrigeration, 2023)

Micropore Structure Changes in Response to H2O2 Treatment of Coals with Different Ranks: Implications for Oxidant Stimulation Enhancing CBM Recovery - Yuan Zhao; Yanjun Meng; Kunjie Li; Sujuan Zhao; Haojie Ma (Natural Resources Research, 2023)

Enlarged fins of Tibetan catfish provide new evidence of adaptation to high plateau - Liandong Yang; Ning Sun; Honghui Zeng; Ying Wang; Wenjun Chen; Zufa Ding; Yang Liu; Jing Wang; Minghui Meng; Yanjun Shen; Jingliang Kang; Xiuhui Ma; et al. (Science China Life Sciences, 2023)

Wheat PHT1;9 acts as one candidate arsenate absorption transporter for phytoremediation - Pengfei Wang; Zedong Chen; Yanjun Meng; Huanting Shi; Chuang Lou; Xu Zheng; Gezi Li; Xiangnan Li; Wanxi Peng; Guozhang Kang (Journal of Hazardous Materials, 2023)

Determination of rock quality designation (RQD) using a novel geophysical approach: a case study - Muhammad Hasan; Yanjun Shang; Xuetao Yi; Peng Shao; He Meng (Bulletin of Engineering Geology and the Environment, 2023)

Critical tectonic events and their geological controls on deep buried coalbed methane accumulation in Daning-Jixian Block, eastern Ordos Basin - Taotao Yan; Shan He; Shuai Zheng; Yadong Bai; Wei Chen; Yanjun Meng; Shangwen Jin; Huifang Yao; Xiaobao Jia (Frontiers of Earth Science, 2023)

Study Regarding the Influence of Blade Rotation Angle Deviations on the Hydraulic Pulsation Characteristics of a Mixed-Flow Pump - Yanjun Li; Danghang Sun; Fan Meng; Yunhao Zheng; Yi Zhong (Journal of Marine Science and Engineering, 2023)
Mixed-flow pumps with adjustable blades are widely used in municipal, agricultural, and hydropower applications. However, a limitation of adjustable blades is that the influence of the water pressure in the pump causes the rotation angle to deviate, which not only reduces the hydraulic efficiency of the pump and increases energy consumption, but it is also detrimental to the stable operation of the pump. To investigate the influence of blade rotation angle deviations (BRADs) on the hydraulic pulsation characteristics of a mixed-flow pump, in this study, a three-dimensional unsteady numerical simulation was adopted to analyze the effects of seven BRAD design schemes on the energy performance, pressure pulsation characteristics, and axial and radial forces in the impeller. When the rotation angle of a single blade deviated counterclockwise, the optimal hydraulic efficiency point of the mixed-flow pump moved toward larger flow rates, and vice versa. Unlike a situation with no BRADs, when there were BRADs, the central symmetry of the low-pressure area near the suction surface of the impeller blades was destroyed. BRADs led to increases in the pressure pulsation amplitudes at the inlet and outlet of the impeller. The dominant pressure pulsation frequencies near the shroud side at the inlet and outlet of the impeller were not affected by BRADs (both of them were equal to the blade frequency). However, the amplitude of the dominant pressure pulsation frequency at the impeller outlet and the radial force of the impeller both increased with increases in the absolute value of the deviation angle. Moreover, when the rotation angle of a single blade was only in the counterclockwise direction, the axial force of the impeller increased. This study can provide an engineering reference for the stability of mixed-flow pumps with BRADs.

A brief review on deer keds of the genus Lipoptena (Diptera: Hippoboscidae) - Nouhoum Dibo; Yanjun Yang; Xiang Wu; Fanming Meng (Veterinary Parasitology, 2023)

Investigation of Energy Losses Induced by Non-Uniform Inflow in a Coastal Axial-Flow Pump - Fan Meng; Yanjun Li; Jia Chen (Journal of Marine Science and Engineering, 2022)
A non-uniform velocity profile occurs at the inlet of a coastal axial-flow pump which is placed downstream of the forebay with side-intake. As a result, the actual efficiency and head of the pump is dissimilar to the design parameters, and the lack of the theoretical investigation on the relationship between inflow distortion and energy losses restricts the application of the coastal axial-flow pump in the drainage project. In this paper, the unsteady numerical simulation and entropy production theory are employed to obtain the internal flow structure and quantify energy losses, respectively, with three inflow deflection angles (θ = 0°, 15°, or 30°). It is reported that the best efficiency point (BEP) shifts to large flow rate with θ increasing, due to the decline of the velocity component in axial direction at the impeller inlet. Therefore, the total entropy production (TEP) of the coastal axial-flow pump rises with θ increasing under small flow rates, but it decreases with θ increasing under large flow rates. The high total entropy production rate (TEPR) in the vicinity of the tailing edge of the impeller and guide vanes rises with θ increasing, caused by the enhanced wake vortex strength. In addition, the high TEPR area near the inlet of outflow conduit rises with θ increasing, originated from the improvement of secondary vortices intensity.

Evaluation of Engineering Rock Mass Quality via Integration Between Geophysical and Rock Mechanical Parameters - Muhammad Hasan; Yanjun Shang; Peng Shao; Xuetao Yi; He Meng (Rock Mechanics and Rock Engineering, 2022)

Physiological Responses of Ribosomal Protein S12 K43 Mutants of Corynebacterium glutamicum - Guihong Zhao; Rui Su; Meng Yuan; Hongkun Ma; Taidong Bo; Hao Jiang; Chen Wu; Yanjun Li (Current Microbiology, 2022)

Identification of MicroRNAs as potential biomarkers for detecting ischemic stroke - Kexin Li; Li Shen; Pingping Zheng; Yanjun Wang; Lijuan Wang; Xiaoli Meng; Yaogai Lv; Zhiqiang Xue; Xin Guo; Anning Zhang; Pan Pan; Chunli Bi; et al. (Genes & Genomics, 2022)

Mooring Stability Study for Novel Wave Energy Converter Based on Regular Wave - Zhongliang Meng; Yun Chen; Yanjun Liu; Yi Ding (Journal of Marine Science and Engineering, 2021)
The mooring system not only plays a vital role in keeping wave energy generators floating stably, but also affects the success of engineering design. Combining wave force theory and the hydrological data obtained from the field measurements of a certain sea area in the Bohai Sea, the Stokes second-order wave theory was adopted to design the mooring system of a new type of power-generating device. At the same time, the study uses the Aqwa software to gather the dynamic data of a power-generating device in a real test, and then makes models and carries out regular wave tests so as to verify the viability of the mooring system and the stability of the whole power-generating device. All of this work will provide a theoretical basis for the manufacture of an engineering prototype and its reliable supply of power.

Contamination assessment, health risk evaluation, and source identification of heavy metals in the soil-rice system of typical agricultural regions on the southeast coast of China - Yanjun Ren; Meng Lin; Qingming Liu; Zhonghao Zhang; Xufeng Fei; Rui Xiao; Xiaonan Lv (Environmental Science and Pollution Research, 2021)

Comparative transcriptomic analysis reveals the mechanistic basis of Pib-mediated broad spectrum resistance against Magnaporthe oryzae - Jiehua Qiu; Feifei Lu; Meng Xiong; Shuai Meng; Xianglin Shen; Yanjun Kou (Functional & Integrative Genomics, 2020)
Rice blast, caused by the fungus Magnaporthe oryzae , is a highly damaging disease. Introducing genes, which confer a broad spectrum resistance to the disease, such as Pib , makes an important contribution to protecting rice production. However, little is known regarding the mechanistic basis of the products of such genes. In this study, transcriptome of the cultivar Lijiangxintuanheigu (LTH) and its monogenic IRBLb-B which harbors Pib treated with M. oryzae were compared . Among the many genes responding transcriptionally to infection were some encoding products involved in the metabolism of ROS (reactive oxygen species), in jasmonate (JA) metabolism, and WRKY transcription factors, receptor kinases, and resistance response signal modulation. The down-regulation of genes encoding peroxiredoxin and glutathione S transferases implied that the redox homeostasis is essential for the expression of Pib -mediated resistance. The up-regulation of seven disease resistance-related genes, including three encoding a NBS-LRR protein, indicated that disease resistance-related genes are likely tend to support the expression of Pib resistance. These data revealed that potential candidate genes and transcriptional reprogramming were involved in Pib -mediated resistance mechanisms.

Permeability dynamic variation of coal under various confining pressures using LFNMR relaxation method - Peng Xia; Fangui Zeng; Xiaoxia Song; Beilei Sun; Taotao Yan; Wei Li; Yanjun Meng (Arabian Journal of Geosciences, 2020)

Structural block division for further deep research in coalbed methane development in the Gujiao area, Xishan coalfield, North China - Peng Xia; Fangui Zeng; Xiaoxia Song; Yanjun Meng; Kunjie Li; Jin Wang; Beilei Sun (Arabian Journal of Geosciences, 2016)

Changes in reference evapotranspiration over an agricultural region in the Qinghai-Tibetan plateau, China - Cungui Zhang; Yanjun Shen; Fenggui Liu; Lei Meng (Theoretical and Applied Climatology, 2016)

Division of the stages of coalbed methane desorption based on the Langmuir adsorption isotherm - Meng YanJun; Tang DaZhen; Qu YingJie; Xu Hao; Li Yong (Arabian Journal of Geosciences, 2015)

Distribution of stable carbon isotope in coalbed methane from the east margin of Ordos Basin - Yong Li; DaZhen Tang; Yi Fang; Hao Xu; YanJun Meng (Science China Earth Sciences, 2014)

Coalbed methane produced water in China: status and environmental issues - Yanjun Meng; Dazhen Tang; Hao Xu; Yong Li; Lijun Gao (Environmental Science and Pollution Research, 2014)

Statistical analysis of the relationship between spring soil moisture and summer precipitation in East China - Lei Meng; Di Long; Steven M. Quiring; Yanjun Shen (International Journal of Climatology, 2014)
The relationship between spring soil moisture ( SM ) and summer precipitation in East China (EC) was examined using monthly temperature and precipitation data and ERA ‐40 SM data. EC was divided into five different climate regions to investigate how SM ‐precipitation correlations vary under different climatic conditions. Both local and remote impacts of spring SM in EC were assessed. It was found that spring SM had significant correlations with summer precipitation in the East, Southeast, and Southwest regions, but not in the Northwest and Northeast region. This is possibly because correlations between summer precipitation and temperature (as a surrogate to SM –evaporation relationship) were statistically significant in the first three regions, but not in the Northwest and Northeast regions. Statistically significant positive correlations between SM and summer precipitation were found in the East and Southeast regions and statistically significant negative correlations were in the Southwest region. The negative SM ‐precipitation relationship is possibly because the Southwest region is primarily an energy‐controlled regime. Significant SM ‐precipitation correlations were usually associated with strong SM persistence and precipitation autocorrelation. Our results suggest that strong correlation between spring SM and summer precipitation might be due to the combination of SM –precipitation interactions and precipitation autocorrelation. Our study also demonstrated that there are strong temporal variations in SM –precipitation relationships in the regions where significant correlations occurred. May SM had significant positive correlations (approximately 0.6) with summer precipitation over most of the study period in East region. Strong negative correlation (approximately −0.6) was found in Southwest during 1980s‐1990s due to strong SM persistence and strong precipitation autocorrelation in the same period. This suggested that SM –precipitation relationships vary over time even in regions with strong coupling. Multivariate regression analysis demonstrated that SM persistence had the largest contribution to summer precipitation variation in East region and April precipitation was the dominant predictor of summer precipitation variations in Southeast and Southwest regions. Statistical analysis of SM and precipitation relationships should consider both SM persistence and precipitation autocorrelation. Results from this study can be used to improve the predictability of droughts.